Przyspieszenie działania algorytmu genetycznego w uczeniu systemów rozmytych - Wasiak, Maciej (Speeding up learning of fuzzy Systems using genetic algorithm, 2005)
One of the biggest problems of machine learning is the speed of finding patterns, extractingrules, etc. The paper considers a problem of teaching fuzzy logic systems using netic algorithm, which has also to select key input variables among their numerous set. Different attempts to speed up the process of learning are presented - mainly unsuccessful. Only one of presented methods gave positive results, speeding up the process more than 50%.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 302-311